2004
DOI: 10.1103/physrevlett.93.016403
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Rates and Lifetime of Exact and Boson Excitons

Abstract: Although excitons are not exact bosons, they are commonly treated as such provided that their composite nature is included in effective scatterings dressed by exchange. We here prove that, whatever these scatterings are, they cannot give both the exciton scattering rates T −1 ij and lifetime τ 0 , correctly: A striking factor 1/2 exists between τ −1 0 and the sum of T −1 ij 's, which originates from the composite nature of excitons, irretrievably lost when they are bosonized. This result, which appears as very… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…To possibly treat their interactions through available many-body procedures -valid for elementary quantum particles only [12,13], -excitons are commonly considered as elementary bosons, their composite nature being hidden through the Coulomb exchange term of the exciton-exciton scattering in the exciton effective Hamiltonian generated by the "bosonization" procedure. In previous works, we have shown that not only the effective exciton-exciton scattering up to now used [14] should have been rejected long ago because it induces an unphysical non hermiticity in the effective exciton Hamiltonian [15], but, worse, there is no way to properly treat the interactions between excitons through an effective potential between elementary bosons, whatever the exciton-exciton scatterings are [9,16]. All our works on exciton many-body effects end with the same conclusion : It is not possible to forget the composite nature of the excitons by reducing them to elementary bosons, whatever the bosonization procedure is.…”
Section: Pacsmentioning
confidence: 99%
See 1 more Smart Citation
“…To possibly treat their interactions through available many-body procedures -valid for elementary quantum particles only [12,13], -excitons are commonly considered as elementary bosons, their composite nature being hidden through the Coulomb exchange term of the exciton-exciton scattering in the exciton effective Hamiltonian generated by the "bosonization" procedure. In previous works, we have shown that not only the effective exciton-exciton scattering up to now used [14] should have been rejected long ago because it induces an unphysical non hermiticity in the effective exciton Hamiltonian [15], but, worse, there is no way to properly treat the interactions between excitons through an effective potential between elementary bosons, whatever the exciton-exciton scatterings are [9,16]. All our works on exciton many-body effects end with the same conclusion : It is not possible to forget the composite nature of the excitons by reducing them to elementary bosons, whatever the bosonization procedure is.…”
Section: Pacsmentioning
confidence: 99%
“…To get the polariton transition rate, we barely follow the procedure we have already used to get the exciton transition rate [9,16]. When H does not split as H 0 + V , the standard form of the Fermi golden rule cannot be used.…”
Section: Polariton Transition Ratementioning
confidence: 99%
“…The transition rate towards another electron-trion state (K e , J ) must be identified with [15,16] t…”
Section: Methodsmentioning
confidence: 99%
“…It turns out that, as briefly rederived below, ξ out in which Coulomb interaction takes place after carrier exchange, does not enter the effective scattering ruling the time evolution of two excitons 35,36 . This is due to a very fundamental reason linked to symmetry breaking in the evolution towards positive time.…”
Section: Introductionmentioning
confidence: 99%